Adaptive Path-following Control of Underactuated Surface Vessels Subject to Unknown Disturbances With Uniform Bounded Lateral Motion - Cao, Duc Sang; Tran, Quoc Van (International journal of control, automation, and systems, 2025)
This article presents a unified framework for path-following and trajectory tracking of underactuated surface vessels (USVs) in the presence of unknown disturbances. To handle the underactuation of the vessel, the path-following of a hand point in the longitudinal axis ahead of the vessel’s mass center is considered. Two robust adaptive path-following control laws are subsequently proposed in the vessel-fixed coordinates to drive the vessel (specifically, the hand point) to the desired path asymptotically. The first controller employs a time-varying discontinuous signum term to attenuate unknown disturbances. By utilization of normalization technique, the second tracking controller is continuous, thus eliminating chattering effect in the control forces commonly occurred in sliding mode controllers. Global uniform asymptotic stability of the path tracking is established based on Lyapunov theory and Barbalat’s lemma. As another technical contribution of this article, the stability of the non-actuated lateral motion of the vessel is shown rigorously based on the square-integrability of the path-following error vector.